2006
DOI: 10.1007/s00405-006-0200-1
|View full text |Cite
|
Sign up to set email alerts
|

Ear wiggling tics: treatment with botulinum toxin injection

Abstract: Ear wiggling tics are a rare disorder and there is no reported satisfactory treatment. We had a patient present with ear wiggling tics, which we treated with injections (totaling 40 units) of botulinum toxin A to the pinna muscle (i.e., the auricularis anterior and superior). The tics completely disappeared within 9 days of injection without any side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 3 publications
1
10
0
1
Order By: Relevance
“…Initially, botulinum toxin injection was used for selected severe cases [3, 107, 125, 229]. Other case reports and case series followed also including children after the age of 8 years [4, 131, 215, 257, 273, 279]. In 35 of 186 patients, botulinum toxin injections were effectively controlling motor tics [8].…”
Section: Pharmacological Treatment Options For Tsmentioning
confidence: 99%
“…Initially, botulinum toxin injection was used for selected severe cases [3, 107, 125, 229]. Other case reports and case series followed also including children after the age of 8 years [4, 131, 215, 257, 273, 279]. In 35 of 186 patients, botulinum toxin injections were effectively controlling motor tics [8].…”
Section: Pharmacological Treatment Options For Tsmentioning
confidence: 99%
“…The current literature on the use of BONT in managing tic disorders is limited to a handful of case reports 6,7 or case series 8,9 and a single small randomised control trial 10 . These studies have addressed patients with vocal tics, ear-wiggling tics or tics of the neck muscles that were idiopathic in nature or associated with Tourette's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…These muscles have been considered vestigial in humans, though it has been suggested that during development in the womb they may exert forces on the cartilage and affect the shaping of the ear ( 2 , 3 ). In postnatal humans, they are rarely under voluntary control ( 2 , 4 ). However, the neural connections of the auricular muscles with the brainstem and other deep brain structures are intact ( 5 7 ), and these muscles are easily accessible for wearable neuroprosthetics.…”
Section: Introductionmentioning
confidence: 99%